(untitled) (Baghdad Science Journal, 2025)
The current study was conductedas a pot experiment to determine the effect of soil texture on biological nitrogen fixation (BNF) of six most efficient local isolates, specified, of Bradyrhizobium. Cowpea (Vignaunguiculata L.), as a legume host crop, was used as a host crop and 15N dilution analysis was used for accurate determination of the amount of N biologically fixed under experimental parameters specified. Soils used are clay loam, sandy clay loam and sandy loam. Biological Nitrogen Fixation (BNF), in different soil textural classes, was as in the following order: medium texture soil > heavy texture soil > light textured soil. Statistical analysis showed that there is a significant variation in BNF % among six Iraqi isolates in the three soil textural classes. There is a significant variation in the number of the nodules of the six Isolates in one soil texture. However, nodules number does not agree with the BNF% in the same soil for any isolates. Statistical analysis of the data showed that there were significant differences in plant dry weight among the soil textural classes all over local isolates used in this study. Data also showed that there were significant differences in dry weight under different isolates.